Politics of the body gender in a neoliberal and neoconservative age - Phipps, Alison (Cambridge, [England] Polity Press, 2014)
Alison Phipps constructs a political sociology of women's bodies around key debates: sexual violence, gender and Islam, sex work and motherhood. Her analysis uncovers dubious rhetorics and paradoxical allegiances, and contextualizes these within the powerful coalition of neoliberal and neoconservative frameworks. She explores how 'feminism' can be caricatured and vilified at both ends of the political spectrum, arguing that western feminisms are now faced with complex problems of positioning in a world where gender often comes second to other political priorities.-- Page 4 of cover.
Keywords: Human body -- Social aspects; Human body -- Political aspects; Gender identity -- Political aspects